Effect of Moringa Oleifera Extract on Behavior Using Male Albino Mice - Suher Aburawi; Muftah Shushni; Mawadda Alkateb (AlQalam Journal of Medical and Applied Sciences, 2021)
Background and objectives: Moringa oleifera belonging to the family of Moringaceae, where it is a monotypic taxon with 13 known species. It is widely growing in tropical and subtropical countries, especially in northwest India, Africa, Arabia, South East Asia, the Pacific, and Caribbean Islands, and South America. The present study deals with the preliminary phytochemical screening and investigates the effect of M. oleifera on behavior by applying the Irwin test and maze; also, to find out if the extract works through benzodiazepine receptor by using Flumazenil as the antagonist. Materials and Methods: The leaves of M. oleifera were collected in (September), 2019 at "Tajoura, Libya. The leaves were removed from other parts then dried in a dark place for 3 days and ground. The crude extract subjected for analysis of the presence of active constituents such as tannins, alkaloids, phytosterols, triterpenoids, flavonoids, cardiac glycosides, saponins, carbohydrates, proteins. The Behavior study was carried out using male albino mice. Mice were randomly assigned to seven groups according to the drug administration, intraperitoneal sub-acute administration was applied (24, 5, 1 hour before scoring). In both experiments, Diazepam (5mg/kg) was used as standard and Flumazenil (0.1mg/kg) was used as a benzodiazepine antagonist. Results: Phytochemical screening indicate the presence of alkaloid, triterpenoid, flavonoid, and carbohydrate in the extract. M. oleifera reduced the SMA, Reactivity, and antagonize each of Restlessness, Irritability, and fearfulness in the Irwin test. The combination of M. oleifera with Flumazenil produced a synergistic decrease of SMA in the Plus maze. Conclusion: Moringa oleifera have a CNS depressant like effect; this effect could be through benzodiazepine receptor because this effect is antagonized by flumazenil. The combination of M. oleifera Extract with Flumazenil produces a synergistic effect toward sedation action. This result needs more study to investigate their mechanism of action. M. oleifera extract does not affect anxiety measure but decreases the SMA. This means that the active constituents in moringa extract may act on BZR1 and not on BZR2.